LKB1 expression and the prognosis of lung cancer: A meta-analysis. Issue 46 (19th November 2021) - Lin, Chunxuan; Lin, Xiaochun; Lin, Kunpeng; Tan, Jialiang; Wei, Chenggong; Liu, Taisheng
Abstract: Background: In the past few decades, many lines of evidence implicate the importance of liver kinase B1 (LKB1) as a tumor suppressor gene in the development and progression of solid tumours. However, the prognostic and clinicopathological value of LKB1 in patients with lung cancer are controversial. This article aimed to investigate the latest evidence on this question. Methods: A systematic literature searched in the PubMed, Web of Science, Embase, Cochrane library, Scopus until September 20, 2020. The association between overall survival (OS), relapse-free survival (RFS), progression-free survival (PFS), clinicopathological features and LKB1 were analysed by meta-analysis. Results: Eleven studies including 1507 patients were included in this meta-analysis. The pooled results revealed that low LKB1 expression was significantly associated with poor overall survival (OS) (HR = 1.67, 95% CI: 1.07–2.60, P  = .024) in lung cancer. However, no association was found between LKB1 expression and DFS/PFS (HR = 1.29, 95% CI: 0.70–2.39, P  = .410). Pooled results showed that low LKB1 expression was associated with histological differentiation (poor vs moderate or well, OR = 4.135, 95% CI:2.524–6.774, P  < .001), nodal metastasis (absent vs present, OR = 0.503, 95% CI: 0.303–0.835, P  = .008) and smoking (yes vs no, OR = 1.765, 95% CI: 1.120–2.782, P  = .014). Conclusion: These results suggest that low expression of LKB1 can be considered as a unfavorable prognostic biomarker for human lung cancer, which should be further researched.